Towards a better understanding of the two neotropical Celtis species: Celtis lancifolia and Celtis tarijensis (Cannabaceae) - Zamengo, Henrique Borges; Chamorro, Debora Cintia; Gaglioti, André Luiz; Demaio, Pablo; Mogni, Virginia Y.; Oakley, Luis J.; Pederneiras, Leandro Cardoso; Prado, Darién E. (Phytotaxa, 2025)
Celtis lancifolia was re-established in the revision of Celtis species native to southern South America. Given that its description does not correspond adjustedly to its type, its status was reevaluated as the characters mentioned actually belong to Celtis tarijensis. For this article, we have updated the taxonomic description of these species and their respective distribution areas.